2018
DOI: 10.1371/journal.pone.0191294
|View full text |Cite
|
Sign up to set email alerts
|

Stockouts of HIV commodities in public health facilities in Kinshasa: Barriers to end HIV

Abstract: Stockouts of HIV commodities increase the risk of treatment interruption, antiretroviral resistance, treatment failure, morbidity and mortality. The study objective was to assess the magnitude and duration of stockouts of HIV medicines and diagnostic tests in public facilities in Kinshasa, Democratic Republic of the Congo. This was a cross-sectional survey involving visits to facilities and warehouses in April and May 2015. All zonal warehouses, all public facilities with more than 200 patients on antiretrovir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 27 publications
0
42
1
Order By: Relevance
“…Third, we did not collect data on drug stockouts during the study. It is possible that many of the women with unsuppressed viral load were simply not taking any medication at the time of the blood collection . Fourth, as mentioned earlier, DBS viral load systematically underestimates plasma viral load , suggesting that the true proportion of women with viral load ≥1000 copies/mL is likely underestimated.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Third, we did not collect data on drug stockouts during the study. It is possible that many of the women with unsuppressed viral load were simply not taking any medication at the time of the blood collection . Fourth, as mentioned earlier, DBS viral load systematically underestimates plasma viral load , suggesting that the true proportion of women with viral load ≥1000 copies/mL is likely underestimated.…”
Section: Discussionmentioning
confidence: 91%
“…However, selection of clinics supported by PEPFAR was not done randomly and because of the cross‐sectional design of the study, it is not possible to ascertain whether this association is a result of PEPFAR selecting clinics that are known to have the capacity to deliver better HIV care or the result of additional technical support to these clinics. Stockouts of HIV commodities including ART are common in health facilities across Kinshasa even when such commodities are available at local upstream warehouses . It is possible that the additional support from PEPFAR, through regular supervision is effective in reducing the impact of such stockouts on ART adherence.…”
Section: Discussionmentioning
confidence: 99%
“…In some settings, the expansion of ART programmes has exacerbated shortages of staff (Nachega et al, 2016), leading to overcrowded HIV clinics and long waiting times for patients attending for drug refills (Idindili et al, 2018). In other contexts, supply chains have not been able to keep up with increasing demands, leading to stock-outs of HIV test kits and antiretroviral drugs (Gils et al, 2018). These strains on the health system may undermine service quality, as overstretched healthcare workers struggle to keep up to date with newly revised protocols and procedures associated with evolving HIV treatment policies (Duncombe et al, 2015;Kwesigabo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies conducted in Africa have revealed that factors affecting ART care are beyond individual level. The factors are related to health care institutions such as lack of ART trained health professionals (31)(32)(33)(34), and lack of quality care (35)(36)(37)(38); community level factors such as stigma (39,40) and traditional healing (41)(42)(43)(44); and program level factors such as political commitment (45,46) and lack of coordinated HIV care activities (47). Nevertheless, comprehensive study has not been carried out in Ethiopia to adequately address the challenges of ART care from the viewpoints of stakeholders.…”
Section: Introductionmentioning
confidence: 99%